The effectiveness of basil extract on the mildew saprolegnia within in vitro - Shara Sasmita; Indah Anggraini Yusanti; Sofian Sofian (JPBIO (Jurnal Pendidikan Biologi), 2021)
Fish disease is a serious problem faced in the aquaculture business. One of the diseases that attack cultured fish is saprolegniasis caused by the fungus Saprolegnia sp. The use of chemical drugs tends to be environmentally unfriendly and has other negative effects on these fish and humans. For this reason, a safer alternative treatment is needed to control fish disease caused by the fungus Saprolegnia sp. One of the plants that have the potential to treat disease caused by the fungus Saprolegnia sp. is basil (Ocimum basilicum L). This research aims to determine the effectiveness of basil extract against the fungus Saprolegnia sp. in vitro. This research was conducted from May to June 2019. The research method used was a completely randomized design (CRD) with 5 treatment levels and 3 replications including 0 ppm (control), 20 ppm, 40 ppm, 60 ppm, and 80 ppm treatments. The test parameter observed was the inhibition zone diameter. In this study, 200 grams of basil extract were produced with 16.67% yield, the conclusion is that basil extract with a concentration of 60 ppm has the largest inhibition zone diameter of 22 mm in inhibiting the growth of the fungus Saprolegnia sp in vitro compared to other ethanol extract concentrations of basil.Keywords: Basil extract, antifungal, saprolegnia sp, in vitro